LOAN WORD: PLAYING WITH WORDS AND CONSONANTAL RADICAL THEORY - Sarage, Japen (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura)
This paper aims at finding out possible ways of relating words in Arabic, English and Indonesian of which their status can be loan words. This kind of study is not possible in the view of historical linguistics since it studies only languages in the same language family. Being a member of language families of Semitic, Indo-European, and Austronesian languages, the three languages are said to be less related. But recent development proposed by Jassem shows that English and Arabic are significantly closely related. The English word rice /rais/ is related to the Arabic word ruzwhere the consonant /r/ is adopted, the vowel /u/ is split into a diphthong /ai/ and the consonant /z/ is weakened into /s/. The same Arabic word is likely adopted into Indonesian beras /bəras/ with two different sound changes i.e. the weakened vowel /u/ into /a/ and the additional sound or syllable /be/ at the beginning. It is a matter of fact that most Indonesian words consist of more than one syllable.The method of analysis in this paper uses Campbell’s theory of sound changes in determining the relationship among Arabic, English and Indonesian words. This method is completed by Jaseem’s theory of Consonantal Radical Theory. Some Arabic, English, and Indonesian words are analyzed by means of Campbell’s theory together with that of Jaseem’s. This paper says nothing about their historical background but provides proofs of word connectedness. This paper may support Jaseem’s theory of Consonantal Radical Theory, which may lead to rethinking of classification of language family